The Prevalence of Oral Complications in Head The Effect of Spacing with Applying Wax on Abutment, on the Retention of Implant Supported Crowns Luted With Different Types of Temporary Cements - A Hafezeqoran; H Sazgara; F Tabatabai (Isfahan University of Medical Sciences, 2007)
Introduction: Some technicians in dental laboratories of Iran have used wax as spacer in implant prosthesis fabrications. This study evaluated the effect of two methods of applying spacer on the retention of implant supported single crowns by using three different provisional cements. Method and Materials: Twenty prepable titanium implant abutments (Biohorizons), with 8mm highth, were placed in implant analogs and torqued to 30 Ncm. Implant analogs were mounted in autopolymerizing acrylic resin blocks using surveyor. Then the Specimens divided into 2 groups. In one group abutments were covered with layer of wax as spacer and in the other one a layer foil 25 μm used as spacer. After wax up and casting of crowns for each abutment, each crowns was pulled from the abutment with a 500 kg load cell in a universal testing machine at a crosshead speed of 0.5 cm/minute, and tensile strength was recorded (N). Provisional luting agents (TempBond, Dycal and TempBond NE) were used to secure the crowns to the respective abutments. All specimens were stored in 100% humidity environment for 48 hours at 37°C prior to testing. Again tensile test was performed in similar manner. Data were analyzed using paired t-test and two-way ANOVA. Results: With using foil as spacer, retention of crowns cemented with Dycal, TempBond NE and TempBond was 24.87 ± 3.91, 21.14 ± 3.02 and 13.96 ± 1.23, respectively. Retention of crowns fabricated with applying wax as spacer was 27.31 ± 2.71 for Dycal, 22.86 ± 2.86 for TempBond NE and 17.24 ± 2.29 for TempBond. With considering each cement separately, there was no significant statistically difference between the mean force required to remove the cemented copings in either test groups (p value > 0.05). Conclusion: Application of wax on abutment as a spacer does not adversely affect the retention of cemented implant supported crowns. Key words: Implant supported prosthesis, spacer, retention, temporary cement.